A laboratory test on the effect of bugholes on surface degradation of tunnel lining concrete subject to freeze–thaw cycles. Issue 21 (8th November 2021) - Hu, Liangjun; Yoshitake, Isamu; Maeda, Tomoyuki
Abstract : Bugholes are usually considered an aesthetic problem rather than a durability problem. Surface bugholes often appear on the sidewalls of a tunnel's lining concrete, which can be mitigated but never eliminated. However, the impact of surface bugholes on concrete durability is still unidentified. In cold regions, the lining concrete of a road tunnel is exposed to de-icer solutions splashed by traffic, and it is additionally exposed to freeze–thaw (F–T) cycles. This study focuses on the durability to F–T cycles of tunnel lining concrete with surface bugholes. For the objectives, the study was carried out on a laboratory-scale F–T test using large concrete blocks. An image analysis based on the RGB values of each pixel in the coloured photographic image was performed to detect and quantify deterioration of the concrete surface throughout the F–T cycles. Although severe scaling never occurred during the 300 F–T cycles, the concrete with bugholes indicated a significant local scaling at the edges of the bugholes. Some bugholes enlarged and some merged with existing bugholes, in accordance with such local scaling. The paper presents synergetic and negative effects of bugholes on the local scaling of tunnel lining concrete exposed to F–T cycles.